The media and the war on terrorism - Hess, Stephen; Kalb, Marvin L. (Brookings Institution Press, 2003)
This collection of conversations between journalists and federal officials aims to capture the tensions between the press and the government during wartime. They cover issues including military censorship and the difficulties of maintaining security in an era of satellite technology.